Implementation of lean practices in small and medium enterprise - Wan Muhammad Shukri , Wan Zainal Abidin (2008)
This thesis deals with the wastes in a SME company which is PJ Foods Industries Sdn. Bhd. The objective of this study is to apply the lean manufacturing concept, principles and tools to eliminate and reduce the occurred wastes in PJ Foods Industries Sdn. Bhd. Movement waste, waiting waste and motion waste were subject that being studied in this thesis. Several visits have been done and the data were collected through interview, observation, pictures and calculating the current total production time of 7kg fried chicken flour product. Materials flow in the original layout, process maps and simulation on the original layout using Witness Software were used to determine the section or process that has highest idle percentage or wastes. Witness Software was also used to simulate the improvement layout and it was found that the improvements on layout managed to eliminate the movement waste and reducing other existing waste as well as reduce the total production time by 2.31% for every 20 packets. For the inventories of finished products, 5S is the best method to improve and establish better workplace and housekeeping conditions. It is recommended that the suggestions in this thesis be applied in actual condition at PJ Foods Industries Sdn. Bhd in the next stage of the study.